2007
DOI: 10.1063/1.2715031
|View full text |Cite
|
Sign up to set email alerts
|

Competition and cooperation between lattice-oriented growth and step-templated growth of aligned carbon nanotubes on sapphire

Abstract: The authors study the growth mechanism of single-walled carbon nanotubes (SWNTs) horizontally aligned on A-plane single crystal sapphire (112¯0) by making the controlled step/terrace structure. SWNT growth direction was sensitive to the surface geometry of the sapphire, and there was competition between two growth modes, lattice-oriented growth and step-templated growth. On the substrate with single-atomic steps, SWNTs aligned parallel to the [11¯00] direction as dominated by the lattice-oriented growth mode, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 20 publications
1
56
0
1
Order By: Relevance
“…Thermal annealing of the substrates in air is necessary before photolithography because thermal treatment of quartz wafers at high temperature greatly decreases the number of OH groups on the surface [25] and thus improves the adhesion between photoresist and quartz wafers. Although thermal annealing for a long time at high temperature can increase the number of the atomic steps on the surface of quartz 6] or sapphire wafers [26], in our observations by AFM (Fig. 2(b)), there were no obvious atomic steps produced on the quartz surface by 1-h thermal treatment.…”
Section: Nano Researchmentioning
confidence: 50%
“…Thermal annealing of the substrates in air is necessary before photolithography because thermal treatment of quartz wafers at high temperature greatly decreases the number of OH groups on the surface [25] and thus improves the adhesion between photoresist and quartz wafers. Although thermal annealing for a long time at high temperature can increase the number of the atomic steps on the surface of quartz 6] or sapphire wafers [26], in our observations by AFM (Fig. 2(b)), there were no obvious atomic steps produced on the quartz surface by 1-h thermal treatment.…”
Section: Nano Researchmentioning
confidence: 50%
“…Interactions with the substrate have previously been exploited in the growth of aligned carbon nanotubes (CNTs) by chemical vapor deposition (CVD). [19][20][21][22][23][24][25] Considering the metalassisted etching as the opposite reaction of the CVD growth process, [ 15,17 ] substrate-induced alignment may also occur in the etching of graphene. A recent study has shown that, under certain circumstances, the interaction with the substrate can effectively infl uence the etching direction.…”
Section: Doi: 101002/adma201302619mentioning
confidence: 99%
“…[19] At present, the control of growth orientation is carried out using specific crystalline substrates, such as sapphire [20,21] or ST-cut quartz surfaces, [15] Although perfect horizontal alignment between SWNTs has been reported using a line-patterned catalyst, the case inevitably has a broad distribution of particle-and tube-diameters in the end. Thus, to accomplish diameter-control of SWNTs and finally use them in nanoelectronic devices, parallel alignment of SWNTs from monodispersed catalytic nanoparticles is an essential step.…”
Section: Resultsmentioning
confidence: 99%